ANALISA UNJUK KERJA KODE SMALL KASAMI PADA DIRECT SEQUENCE SPREAD SPECTRUM YANG MENERAPKAN KODE KANAL BCH PADA KONDISI KANAL FREKUENSI SELEKTIF FADING - Aldi Rae G, Komang; Pramaita, Nyoman; Diafari Djuni H, I Gst A. Komang (Jurnal SPEKTRUM, 2025)
This study analyzes the performance of the small Kasami spread spectrum code on the Direct Sequence Spread Spectrum (DSSS) system that implements and does not implement the Bose Chaudhuri Hocquenghem (7,4) (BCH (7,4)) channel code under AWGN channel and frequency selective fading conditions. Simulation of the application of the BCH (7,4) code on DSSS-Small Kasami under AWGN channel and frequency selective fading conditions is analyzed based on the Bit Error Rate (BER) versus Energy Bit per Noise Density (EbNo). The application of the BCH (7,4) code on DSSS-Small Kasami under frequency selective fading channel conditions with a delay spread that is much narrower than the length of the Small Kasami code, produces better performance than that of DSSS-Small Kasami without BCH (7,4) channel coding. However, under conditions where the delay spread of the fading channel is wider than the length of the Small Kasami code, the application of the BCH (7,4) channel code has almost the same performance as without the application of the BCH (7,4) channel code. This is caused by the increasing multipath components (widening delay spread) causing more autocorrelation values on the Small Kasami code ACF graph, so that more interference signals will interfere with the desired signal. Under this condition, both those implementing the BCH (7,4) channel code and those not have decreased performances.